2017
DOI: 10.1055/s-0037-1608625
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Elective Hand Surgery

Abstract: ). AbstractPurpose Antibiotic prophylaxis decreases the rate of surgical site infection in a broad spectrum of surgical procedures. However, in patients undergoing elective hand surgery, there is evidence of lower efficacy, and its use might be related to the development of antimicrobial resistance. The side effects and higher health-related costs must also be taken into consideration. Our aim was to assess the efficacy of antibiotic prophylaxis in these procedures. Material and methods A retrospective study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A recent study evaluated the association between diabetes mellitus and surgical site infections in 346 patients undergoing clean, elective hand surgical procedures lasting <30 minutes. In this cohort, only 4 patients developed a surgical site infection and only 1 of those patients who developed a surgical site infection had diabetes mellitus, leading the authors to conclude that diabetes did not affect the rate of surgical site infection 58 . Ko et al attempted to address whether preoperative antibiotic prophylaxis reduces surgical site infections in patients with diabetes mellitus undergoing carpal tunnel release.…”
Section: Special Scenarios Host Factorsmentioning
confidence: 86%
“…A recent study evaluated the association between diabetes mellitus and surgical site infections in 346 patients undergoing clean, elective hand surgical procedures lasting <30 minutes. In this cohort, only 4 patients developed a surgical site infection and only 1 of those patients who developed a surgical site infection had diabetes mellitus, leading the authors to conclude that diabetes did not affect the rate of surgical site infection 58 . Ko et al attempted to address whether preoperative antibiotic prophylaxis reduces surgical site infections in patients with diabetes mellitus undergoing carpal tunnel release.…”
Section: Special Scenarios Host Factorsmentioning
confidence: 86%
“…Hand. With regards to antibiotic-prophylaxis in hand surgery, Vasconcelos et al 14 study show no difference in SSI incidence after administration of prophylaxis or placebo in clean surgery that lasted less than 30 minutes. The procedures that would not require antibiotic therapy are skin incision, soft tissue excision, suturing, and repairing of tearing of muscle, tendon, and fascia 5 .…”
Section: Clinical Applicationsmentioning
confidence: 96%
“…Vasconselos and colleagues conducted a retrospective review of 346 patients (50 had DM) who underwent clean, elective, outpatient hand surgery. 35 Preoperative antibiotics were given at the discretion of the attending surgeon to 180 (52%) of the total number and to 27 (54%) of the patients with diabetes. There were 4 SSI cases (1% infection rate), and 1 of these was a patient with diabetes.…”
Section: Role Of Prophylactic Antibiotics For Patients With Diabetes ...mentioning
confidence: 99%
“…In a different study, Werner et al reviewed 454 987 Medicare patients in a national administrative database and identified 1466 postoperative infections following open CTR (0.32%). 28 Among the independent positive risk factors identified were male sex, younger age, tobacco use, alcohol use, obesity (body mass index of [30][31][32][33][34][35][36][37][38][39][40], morbid obesity (body mass index: >40), and comorbidities including DM, inflammatory arthritis, peripheral vascular disease, chronic liver disease, chronic lung disease, chronic kidney disease, and depression.…”
Section: Association Between Dm and Ssis Following Hand Surgerymentioning
confidence: 99%